Global management of patients with knee osteoarthritis begins with quality of life assessment: a systematic review - Vitaloni, Marianna; Botto-van Bemden, Angie; Sciortino Contreras, Rosa Maya; Scotton, Deborah; Bibas, Marco; Quintero, Maritza; Monfort, Jordi; Carné, Xavier; de Abajo, Francisco; Oswald, Elizabeth; Cabot, Maria R.; Matucci, Marco; et al. (BMC musculoskeletal disorders, 2019)
Background Knee osteoarthritis (KOA) is a prevalent form of chronic joint disease associated with functional restrictions and pain. Activity limitations negatively impact social connectedness and psychological well-being, reducing the quality of life (QoL) of patients. The purpose of this review is to summarize the existing information on QoL in KOA patients and share the reported individual factors, which may influence it. Methods We conducted a systematic review examining the literature up to JAN/2017 available at MEDLINE, EMBASE, Cochrane, and PsycINFO using KOA and QOL related keywords. Inclusion criteria were QOL compared to at least one demographic factor (e.g., age, gender), lifestyle factor (e.g., functional independence), or comorbidity factor (e.g., diabetes, obesity) and a control group. Analytical methods were not considered as part of the original design. Results A total of 610 articles were reviewed, of which 62 met inclusion criteria. Instruments used to measure QoL included: SF-36, EQ-5D, KOOS, WHOQOL, HAS, AIMS, NHP and JKOM. All studies reported worse QoL in KOA patients when compared to a control group. When females were compared to males, females reported worse QOL. Obesity as well as lower level of physical activity were reported with lower QoL scores. Knee self-management programs delivered by healthcare professionals improved QoL in patients with KOA. Educational level and higher total mindfulness were reported to improve QoL whereas poverty, psychological distress, depression and lacking familial relationships reduce it. Surgical KOA interventions resulted in good to excellent outcomes generally; although, results varied by age, weight, and depression. Conclusion KOA has a substantial impact on QoL. In KOA patients, QoL is also influenced by specific individual factors including gender, body weight, physical activity, mental health, and education. Importantly, education and management programs designed to support KOA patients report improved QoL. QoL data is a valuable tool providing health care professionals with a better comprehension of KOA disease to aid implementation of the most effective management plan.